Los efectos adversos de la minería en la economía - Gomero Gonzales, Nicko Alberto (2015)
The countries that have supported its development based on innovation, knowledge, science and technology have achieved much more favorable results than those only having focused their macro and micro economy in extraction activities such as mining. The instability of this sector and its attachment to the international scene determines that the indicators of economic growth also have the same behavior. That is, its sustainability is correlated to signs of the global economy, especially those countries demanding raw materials. Moreover, expenses and investments in social projects such as the same budgetary resources, are subject to the vagaries of international prices of minerals. Furthermore, studies have shown that governments with more corruption, are those with abundant natural resources, which by the way, also constitute the starting point of the social convulsions observed.